2001
DOI: 10.1093/eurpub/11.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among children aged 2-17 years in the five Nordic countries: Comparison between 1984 and 1996

Abstract: Nordic children still enjoy a high standard of living in spite of economic constraints, and the prerequisites for a high QoL are fulfilled. Further research is suggested for clarifying the complex background of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 0 publications
2
62
0
1
Order By: Relevance
“…The results from the NordChild study have been widely published in scientific journals, as summary reports and as doctoral theses. [1][2][3][4][5][6][7][8][9] The general results from these studies confirmed the good health, the high living standard and the excellent prerequisites for a proper quality of life among Nordic children. [3,5,10,11] However, the results also showed an increase of long term illness (LTI) in children aged 2-17 years from 7.9% in 1984 to 14.6% in 1996 [6] and to 17.8% in 2011.…”
Section: Introductionmentioning
confidence: 64%
“…The results from the NordChild study have been widely published in scientific journals, as summary reports and as doctoral theses. [1][2][3][4][5][6][7][8][9] The general results from these studies confirmed the good health, the high living standard and the excellent prerequisites for a proper quality of life among Nordic children. [3,5,10,11] However, the results also showed an increase of long term illness (LTI) in children aged 2-17 years from 7.9% in 1984 to 14.6% in 1996 [6] and to 17.8% in 2011.…”
Section: Introductionmentioning
confidence: 64%
“…In ei ner neue ren dä ni schen Stu die [66] konn ten kei ne Zu sam men hän-ge zwi schen Schicht zu ge hö rig keit und jugend li chen Rücken schmer zen nach ge wiesen wer den. Dem ge gen über war das Auftre ten chro ni scher Er kran kun gen bei Kindern mit Zu ge hö rig keit zur un te ren so zialen Schicht be deut sam kor re liert [8]. Die Wahr schein lich keit, Schmer zen zu ha ben, ist für Kin der, die in Ar bei ter fa mi li en mit ge rin gem Bil dungs ni veau und ge rin gem Ein kom men le ben, nach den Er geb nis sen ei ner skan di na vi schen Stu die fast 1,4fach er höht [23].…”
Section: Fa MI Lie/so Zia Le Um Ge Bungunclassified
“…There are fewer studies looking at this specific population, adolescents are most often grouped in with either children or adults. However, the studies that have subanalyses of adolescents or focus exclusively on adolescents have noted an overall decline in HRQL among adolescents along with a more negative perspective of their HRQL [6][7][8] . Compared to all other age groups, adolescents have been found to have notable differences in physical maturation, body image, peer relationships, intimacy, sexuality, and autonomy [9] .…”
Section: Introductionmentioning
confidence: 99%